Perbandingan Konstitusi Negara Indonesia Dan Rusia - Ilham Dwi Rafiqi (Widya Yuridika, 2022)
The purpose of this study is to analyze and compare the state constitutions of Indonesia and Russia, particularly in relation to state institutions, separation of powers, and institutions for interpreting the constitution. This study uses a normative juridical research method with a statutory approach and a comparative approach. The results of the study show that in terms of institutions, Indonesia and Russia both adhere to the trias politica separation. However, in terms of the government system, there are differences, if Indonesia adheres to a purely presidential system of government, the Russian Federation adheres to semi-presidential. As for the institutions of interpreting the constitution, there are also similarities and differences. Similarities such as being an interpreter of the constitution, being a dispute resolution institution for state institutions to providing opinions on impeachment. The difference is that if the Constitutional Court of the Republic of Indonesia has the authority to decide on the dissolution of political parties and disputes regarding the results of the general election, the Constitutional Court of the Russian Federation does not have that authority. On the other hand, the Constitutional Court of the Russian Federation does not have the authority, for example, to receive complaints about violations of constitutional rights, to decide on the constitutionality of agreements between Russian state government agencies, and to decide on the normative actions of Russian state officials.